The amino acid transporter SLC7A5 confers a poor prognosis in the highly proliferative breast cancer subtypes and is a key therapeutic target in luminal B tumours - El Ansari, Rokaya; Craze, Madeleine L.; Miligy, Islam; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ellis, Ian O.; Rakha, Emad; Green, Andrew R. (BioMed Central, 2018)
Background: Breast cancer (BC) is a heterogeneous disease characterised by variant biology and patient outcome. The amino acid transporter, SLC7A5, plays a role in BC although its impact on patient outcome in different BC subtypes remains to be validated. This study aimed to determine whether the clinicopathological and prognostic value of SLC7A5 is different within the molecular classes of BC. Methods: SLC7A5 was assessed at the genomic, using METABRIC data (n=1,980), and proteomic, using immunohistochemistry and TMA (n= 2664; 1,110 training and 1,554 validation sets), levels in well-characterised primary BC cohorts. SLC7A5 expression was correlated with clinicopathological and biological parameters, molecular subtypes, and patient outcome. Results: SLC7A5 mRNA and protein expression were strongly correlated with larger tumour size, and higher grade. High expression was observed in triple negative (TN), HER2+, and luminal B subtypes. SLC7A5 mRNA and protein expression was significantly associated with the expression of the key regulator of tumour cell metabolism c-MYC, specifically in Luminal B tumours only (p=0.001). High expression of SLC7A5 mRNA and protein was associated with poor patient outcome (p <0.001) but only in the highly proliferative ER+/ luminal B (p=0.007) and HER2+ classes of BC (p=0.03). In multivariate analysis, SLC7A5 protein was independent risk factor for shorter Breast Cancer Specific Survival only in ER+ high proliferation tumours (p=0.02). Conclusions: SLC7A5 appears to play a role in the aggressive highly proliferative ER+ subtype driven by MYC and could act as a potential therapeutic target. Functional assessment is necessary to reveal the specific role played by this transporter in the ER+highly proliferative subclass and HER2+ subclass of BC.